How Can Social Attitudes Cultivate During Online Learning in Elementary School? - Abduh, Muhammad; Zainuddin, Almuntaqo; Wardana, Krisna Pandu (Proceedings International Conference on Education Innovation and Social Science, 2022)
Social attitude competence is essential to be integrated in learning. So it is very necessary to learn how to cultivate the competence of social attitudes in the online learning process. This research aims to describe the efforts, obstacles and solutions of elementary teachers in Semarang Regency in instilling social attitude competence during online learning. This type of research is qualitative research. Respondents in this study were 72 elementary school teachers in Surakarta. Data collection techniques use open questionnaires. Data analysis isdone with thematic analysis using the help of NVivo 12 plus software. The results showed that teachers plan to cultivate social attitude competencies by preparing an integrated lesson plan content of social attitudes through habituation, assignment, group activities, and environmental utilization and time discipline. While the cultivation of social attitude competence during online learning is done through several efforts, namely by providing teaching materials charged with social attitudes, habituation, considering timeliness in sending tasks, utilizing the surrounding environment, group work and suppressing time discipline.